Internet connectivity disruption in Hungary (Hungary) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Hungary. Data sourced from IODA.
Network Disruption Incident ID: HU-2026-0014. Severity: critical. Confidence: 67%